PENGARUH LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI DENGAN PERILAKU KEUANGAN SEBAGAI VARIABEL MODERASI PADA MAHASISWA DI KOTA DENPASAR - UPAYANA WIGUNA EKA SAPUTRA; I KETUT YASA; IDA BAGUS DANANJAYA; NI PUTU RITA SINTADEVI; ANAK AGUNG RAKA SITAWATI; NI LUH MADE WIJAYATI; GEDE SEDANA WIBAWA YASA (GANEC SWARA, 2023)
This study attempted to examine the influence that financial literacy has on investment decisions and how that effect can be tempered by the financial behavior of college students in Denpasar City. Specifically, this study focused on college students in Denpasar City. This study involved quantitative methods. There were 130 pupils from the Denpasar City region that made up the sample population. Primary data were used in the analysis, which was conducted using the PLS-based structural equation modeling approach. The method of collecting data makes use of a questionnaire that is scored on a Likert scale and is submitted using a Google Form. The data are collected using a Purposive Sampling approach. According to the findings of the study, having a strong understanding of personal finance has a large and favorable impact on investment choices. Then, one's financial behavior can have an effect on the connection between financial literacy and investing choices.